2021
DOI: 10.1002/cncr.33849
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of patient‐reported xerostomia among long‐term oropharyngeal cancer survivors

Abstract: Background This study was conducted to identify clinicodemographic risk factors for xerostomia among long‐term oropharyngeal cancer (OPC) survivors. Methods This cross‐sectional study included 906 disease‐free, adult OPC survivors with a median survival duration at the time of survey of 6 years (range, 1‐16 years); self‐reported xerostomia scores were available for 877 participants. Study participants had completed curative treatment between January 2000 and December 2013 and responded to a survey administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…A retrospective study from 2017 with 63 head-and-neck cancer patients also identified the addition of chemotherapy (p<0.05) as a risk factor of xerostomia (13). In a large retrospective cross-sectional study from 2021, patientreported data regarding xerostomia were available for 877 long-term survivors after treatment of oropharynx cancer (9). Approximately 99% of these patients had received radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study from 2017 with 63 head-and-neck cancer patients also identified the addition of chemotherapy (p<0.05) as a risk factor of xerostomia (13). In a large retrospective cross-sectional study from 2021, patientreported data regarding xerostomia were available for 877 long-term survivors after treatment of oropharynx cancer (9). Approximately 99% of these patients had received radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, this can often only be realized if the distribution of the radiation dose at the target volume is compromised, which may result in a higher risk of a locoregional recurrence of the cancer. Several clinical factors have been reported as predictors of xerostomia after radiotherapy of head-and-neck cancers including tumor site (oropharynx, oral cavity), advanced stage, bilateral involvement of lymph nodes and/or irradiation, more advanced age, and concurrent systemic therapies (9)(10)(11)(12)(13). Regarding the impact of dose-volume parameters of radiotherapy on xerostomia, the mean dose to parotid glands was identified as significantly associated with the risk of xerostomia in several studies (10,(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Therefore, we also abstracted information on mean dose to parotid glands from medical charts and, using the threshold dose, categorized mean parotid gland dose as follows; ≤ 26 Gy, > 26 Gy, and missing/don’t know. Cigarette smoking status was determined as follows: participants who had not smoked 100 cigarettes in their lifetime were classified as never smokers, those who had quit more than 6 months before diagnosis were considered former smokers at the time of diagnosis 20 , 29 , 30 and finally, current smokers at the time of diagnosis were further categorized into those who quit subsequently and those who continued to smoke 9 , 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive statistics were used to summarize the study data and the Kruskal Wallis test and Fishers exact test were used to test for differences between xerostomia categories for continuous and categorical variables, respectively. In a larger study, we had found that sex, education, cigarette smoking, and radiotherapy type were significantly associated with xerostomia; therefore, we adjusted our genetic analyses with these covariates 9 along with mean dose to parotid glands 28 . Quality control for genotype data in our study included: removing SNPs with Hardy–Weinberg equilibrium (HWE; P < 1 × 10 –6 ), genotyping typing call rate ≤ 95%, and minor allele frequency ≤ 0.05 among OPC patients 24 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation